Symbolism Matters: The Effect of Same-Sex Marriage Legalization on Partnership Stability - Shuai Chen; Jan C. van Ours (Institute of Labor Economics (IZA), 2019)
We study the effect of marriage on the stability of formal partnerships exploiting same-sex marriage legalization in the Netherlands as a natural experiment. Same-sex marriage legalization allowed registered partnerships to be transformed into marriage. Since registered partnerships and marriages are similar in terms of rights and obligations we can investigate the effect of marital symbolism on the partnership stability. Using rich administrative data, we find that same-sex marriage legalization had two different effects. First, it increased the separation rate of existing same-sex registered partnerships. Second, partnerships that were transformed into marriage had a substantially lower separation rate. We take the second finding as evidence of the symbolic effect of marriage stabilizing partnerships.
Keywords: D78; J12; J15; J16; K36; 330; same-sex marriage; registered partnership; separation; duration analysis